Prevalence of dental caries and caries-related risk factors in premature and term children - Vanessa Resende Nogueira Cruvinel; Danuze Batista Lamas Gravina; Tatiana Degani Paes Leme Azevedo; Ana Cristina Barreto Bezerra; Orlando Ayrton de Toledo (Sociedade Brasileira de Pesquisa Odontológica, 2010)
This study evaluated the prevalence of enamel defects and dental caries and their risk factors on primary and permanent dentitions of prematurely-born children and term children. Eighty children were examined, 40 born prematurely (G1) and 40 born term (G2), in the age group between 5 and 10 years. The demographic variables, medical history and oral health behaviors were recorded on a questionnaire. The teeth were examined for presence of deficiencies of the enamel and caries that were registered. The caries were registered, focusing on the indices dmft (decayed, missing, and filled primary teeth) and DMFT (decayed, missing, and filled permanent teeth). The results showed that 75% of the total sample had enamel defects. The logistic regression model showed that other risk factors such as per capita family income, educational level, dietary and hygiene habits, fluoride exposure, trauma, and diseases had no correlation with enamel defects and caries. A smaller value of total DMFT (0.95) was found in the group of premature children in comparison to the term children (2.07) p = 0.0164. There was no difference concerning the permanent dentition between the two groups (p = 0.9926). One concludes that prematurity can't be a predisposing factor for the presence of dental caries.